Brønsted Acid Catalyzed Asymmetric Silylation of Alcohols - Hyodo, Kengo; Gandhi, Shikha; van Gemmeren, Manuel; List, Benjamin (Synlett, 2015)
We report a catalytic enantioselective desymmetrization of meso-1,2-diols by monosilylation using a chiral enantiopure Brønsted acid as catalyst and hexamethyldisilazane (HMDS) as silyl source.
Keywords: enantioselective Brønsted acid catalysis; silyl transfer; meso-diols; desymmetrization; asymmetric counteranion-directed catalysis (ACDC)